2010
DOI: 10.1016/j.drugalcdep.2009.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation on sleep homeostasis and restoration during methadone-maintenance: A [31]P MRS brain imaging study

Abstract: SUMMARYInsomnia afflicts many individuals, but particularly those in chronic methadone treatment. Studies examining sleep deprivation (SD) have begun to identify sleep restoration processes involving brain bioenergetics. The technique [31]P magnetic resonance spectroscopy (MRS) can measure brain changes in the high-energy phosphates: alpha-, beta-, and gamma-nucleoside triphosphate (NTP). In the present study, 21 methadone-maintained (MM) and 16 control participants underwent baseline (BL), SD (40 wakeful hrs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 109 publications
(113 reference statements)
1
18
1
Order By: Relevance
“…One study noted reduced levels of phosphocreatine found in the orbitofrontal and occipital cortices in heroin users initiating methadone maintenance therapy but not in a healthy comparison group (Silveri et al, 2004), whereas another study demonstrated no differences in concentrations of whole brain phosphocreatine in individuals on methadone maintenance therapy compared with healthy controls (Trksak et al, 2010). Length of methadone maintenance therapy might explain the discrepancy in these findings, as in one of the studies, methadone was recently initiated (Silveri et al, 2004), while in the other study, the duration of methadone maintenance ranged from 8 to 28 months (Trksak et al, 2010). Because of the limited number of MRS studies in opiate use, it is difficult to assess the impact of opiate use on the brain; however, the few published reports provide some evidence that there are differences in neurochemistry in opiate users starting opiate maintenance therapy in comparison to nonopiate users.…”
Section: Resultsmentioning
confidence: 99%
“…One study noted reduced levels of phosphocreatine found in the orbitofrontal and occipital cortices in heroin users initiating methadone maintenance therapy but not in a healthy comparison group (Silveri et al, 2004), whereas another study demonstrated no differences in concentrations of whole brain phosphocreatine in individuals on methadone maintenance therapy compared with healthy controls (Trksak et al, 2010). Length of methadone maintenance therapy might explain the discrepancy in these findings, as in one of the studies, methadone was recently initiated (Silveri et al, 2004), while in the other study, the duration of methadone maintenance ranged from 8 to 28 months (Trksak et al, 2010). Because of the limited number of MRS studies in opiate use, it is difficult to assess the impact of opiate use on the brain; however, the few published reports provide some evidence that there are differences in neurochemistry in opiate users starting opiate maintenance therapy in comparison to nonopiate users.…”
Section: Resultsmentioning
confidence: 99%
“…These data were collected as part of a larger study assessing effects of SD on sleep architecture (polysomnography) and brain bioenergetics (magnetic resonance spectroscopy) (Trksak et al, 2010). These previous analyses found no effect of methadone dose, but an effect of MM duration with long-term MM participants recovering from SD more similarly to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, participants on a high dose of methadone would perform the most poorly, however after SD both high- and low-dose groups would perform at a similar level. These data were collected as part of a larger study to assess the effects of SD on sleep architecture and brain bioenergetics in MM participants (Trksak et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In a study of opioid naïve individuals, sleep architecture was significantly altered after a single opioid medication administration, with participants evidencing increases in the percentage of time spent in light sleep stages, and a marked reduction in the percentage of time spent in deep sleep stages (Dimsdale et al, 2007). Multiple mechanisms of action leading to disturbed sleep in those abusing opioids have been theorized, including decreased REM sleep (Lydic and Baghdoyan, 2005), altered GABA functioning (Watson et al, 2007), and lowered levels of adenosine (Trksak et al, 2010). Though sleep has become a focus of substance use research, no known studies to date have utilized actigraphy with a group of current PO dependent individuals.…”
Section: Introductionmentioning
confidence: 99%